2023
DOI: 10.3390/healthcare11020161
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Short-Video Problematic Use, Learning Engagement, and Perceived Learning Ineffectiveness among Chinese Vocational Students

Abstract: Short videos are very popular among students, but the immersive nature of the software makes them prone to problematic use and even addiction. Internet addiction, including short-video problematic use, has been a hot topic in recent years due to the COVID-19 epidemic. However, there are few empirical studies that have explored the effects of short-video problematic use on students. Thus, vocational colleges in China were recruited to participate in this study. There were 1089 effective participants, with a val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Another study showed that both short video flow and short video addiction had significant negative relationships with achievement motivation in vocational school students (12). Moreover, it is known that short video addiction has positive significant relationships with learning avoidance motivation and negative significant relationships with learning commitment in vocational school students (45). Therefore, it can be said that studies showing the negative effects of short video flow and addiction on students are similar to the findings of this study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Another study showed that both short video flow and short video addiction had significant negative relationships with achievement motivation in vocational school students (12). Moreover, it is known that short video addiction has positive significant relationships with learning avoidance motivation and negative significant relationships with learning commitment in vocational school students (45). Therefore, it can be said that studies showing the negative effects of short video flow and addiction on students are similar to the findings of this study.…”
Section: Discussionsupporting
confidence: 84%
“…It is known that students' learning motivation, achievement motivation and learning well-being have negative significant correlations with short video flow experience and short video addiction (12,20). In addition, problematic use of short videos negatively affects the behavioral engagement required for academic success (21). Short video addiction predicts individuals' creative self-efficacy, creative self-confidence, career interests and academic learning environments (22).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the teaching mode of Chinese universities, teachers have absolute control, while students are passive recipients of knowledge in the most classrooms in universities. In addition, Chinese students are often the ‘silent ones’ in the classroom, rarely expressing their own opinions (Li, 2022; Ye et al., 2023). Students are chronically passive and lack a sense of control and involvement in the classroom, which leads to a sense of boredom.…”
Section: Discussionmentioning
confidence: 99%
“…This problematic usage is generally considered to be detrimental to users. Students in particular love short videos, but because of the immersive nature of the videos, many students can experience associated problems, and some even become addicted [ 2 , 3 , 4 ]. Therefore, Hong et al pointed out that video addiction behaviors have had a very large negative impact on the study and life of students of different school ages [ 5 ].…”
Section: Introductionmentioning
confidence: 99%